2023
DOI: 10.1161/circimaging.122.014071
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Targets to Visualize the Cardiac Immune Landscape in Heart Failure

Abstract: Heart failure involves a complex interplay between diverse populations of immune cells that dynamically shift across the natural history of disease. Within this context, the character of the immune response is a key determinant of clinical outcomes. Recent technological advances in single-cell transcriptomic, spatial, and proteomic technologies have fueled an explosion of new and clinically relevant insights into distinct immune cell populations that reside within the diseased heart including potential targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Consistent with their functions, mitochondrial proteins and lipid metabolism-related proteins were more abundant in healthy ventricles than in atria [ 11 ]. An increasing number of studies have reported that immune activation and inflammation are considered important drivers of cardiac remodeling and HF [ 30 , 31 ]. Interestingly, we found that the proteins that were specifically upregulated in the atria of HF samples were mainly enriched in the complement and coagulation cascades, which cause overt inflammation, thrombotic microangiopathy and end-organ damage [ 32 34 ]; however, the proteins that were specifically upregulated in the ventricles of HF samples were mainly enriched in the FoxO signaling pathway, which is involved in maintaining cardiomyocytes in the homeostatic state and inducing their adaptation to metabolism [ 35 , 36 ], and the apelin signaling pathway, which plays a critical role in the positive inotropic effect and maintains cardiac contractility [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their functions, mitochondrial proteins and lipid metabolism-related proteins were more abundant in healthy ventricles than in atria [ 11 ]. An increasing number of studies have reported that immune activation and inflammation are considered important drivers of cardiac remodeling and HF [ 30 , 31 ]. Interestingly, we found that the proteins that were specifically upregulated in the atria of HF samples were mainly enriched in the complement and coagulation cascades, which cause overt inflammation, thrombotic microangiopathy and end-organ damage [ 32 34 ]; however, the proteins that were specifically upregulated in the ventricles of HF samples were mainly enriched in the FoxO signaling pathway, which is involved in maintaining cardiomyocytes in the homeostatic state and inducing their adaptation to metabolism [ 35 , 36 ], and the apelin signaling pathway, which plays a critical role in the positive inotropic effect and maintains cardiac contractility [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%